Preparation of a guide for hospitalized diabetic pharmacological management in the Internal Medicine Service - Luis Alberto Corona Martínez; Laydamí Rodríguez Amador; Ramón Ricardo Vélez Pérez; Sandra Borroto Lecuna; Caridad Hernández Abreus (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: The medical care of diabetics hospitalized in Internal Medicine Service wards of the Gustavo Aldereguía Lima Hospital, Cienfuegos, is characterized by a great variability in the performance, determined by criteria and very personal approaches of the physicians. Objective: to develop a guide for the pharmacological management of diabetics with poor metabolic control or a state of uncomplicated acute hyperglycemia, hospitalized in the Internal Medicine Service. Methods: a study which included a bibliographic review, from which a first version of the guide was elaborated, later discussed in the staff of the Internal Medicine Service of the Dr. Gustavo Aldereguía Lima Hospital, in Cienfuegos. In the group discussions the criticisms and suggestions to the proposal were registered. Finally, the document was prepared. Results: among the most important actions proposed by the guide, was the patient stratification of into four different groups according to the degree of metabolic control at admission, or due to their condition of disease debut. In addition, a particular pharmacological therapeutic behavior was suggested for each of these four groups. In the case of patients admitted due to poor metabolic control or uncomplicated acute hyperglycemia, the "scheduled subcutaneous insulin therapy" scheme was introduced. The metabolic objectives to be achieved were specified, as well as the diagnostic and therapeutic aspects related to hypoglycemia. Conclusion: the Guide for diabetic care can be very useful in all non-critical services (including surgical ones), where these patients are very frequently admitted.